Development of horizontal bulb hydroturbines for high heads with a wide range of reliable operation modes - Krupa, Y. S. (Національний технічний університет "Харківський політехнічний інститут", 2022)
The issues and directions for improving the energy-cavitation and operational performance of hydro turbine equipment of hydroelectric power plants are considered. The paper analyzes in detail the directions for improving the main indicators characterizing the energy and operational advantages of horizontal hydro turbines. Straight-axis Kaplan hydraulic turbines with a horizontal axis of rotation of the hydraulic unit have incomparable advantages compared to hydraulic turbines with water supply using a spiral case, in terms of higher throughput and a wider range of operation. The practice of hydraulic turbine construction has determined the range of heads for which different types of hydraulic turbines are used. The use of horizontal direct flow hydraulic turbines for heads of more than 40 meters encounters a number of problems of a hydrodynamic nature, strength, and reliable operation. The paper analyzes the advantages of direct-flow bulb hydro turbines and the possibility of using them for high heads. New design solutions are considered, for which Ukrainian patents have been obtained, allowing the use of horizontal bulb hydraulic units for higher heads (up to 300 meters) and at the same time obtaining a wider operating area not only in terms of flow rates, but also in terms of heads. The use of twin bulb hydraulic units will significantly expand the operational ranges of highly efficient and reliable operation of horizontal bulb hydraulic turbines at flow rates (power) that allow them to successfully operate at variable peak loads of daily regulation. Based on the analysis of the working process of various horizontal and diagonal turbines, the analysis of their universal characteristics, scientifically based proposals was developed for the nomenclature of twin bulb hydraulic units. The design of a horizontal hydraulic turbine using inlet nozzle channels is presented. The use of nozzle diaphragms as elements that create the angular momentum necessary for optimal operation of the hydraulic turbine makes it possible to use bulb direct-flow hydro units for high heads (80–100 meters).

Розглянуті питання та напрями підвищення енергокавітаційних та експлуатаційних показників гідротурбінного обладнання гідроелектростанцій. Докладно проаналізовано напрями удосконалення основних показників, що характеризують енергетичні та експлуатаційні переваги лопатевих гідротурбін горизонтального типу. Прямовісні повортно-лопатеві гідротурбіни з горизонтальним розташуванням осі обертання гідроагрегату мають незрівнянні переваги в порівнянні з гідротурбінами з підведенням води за допомогою спіральної камери, в частині більш високої пропускної здатності і ширшого діапазону експлуатації. Практика гідротурбобудування визначила діапазон напорів, на які застосовуються різні типи гідротурбін. Застосування горизонтальних прямоточних гідротурбін на напори понад 40 метрів зустрічає ряд проблем гідродинамічного характеру, міцності, а також проблем надійної експлуатації. Проаналізовано переваги прямоточних капсульних гідротурбін та можливість їх застосування на високі напори. Розглянуто нові конструктивні рішення, на які отримано патенти України, що дозволяють застосовувати горизонтальні капсульні гідроагрегати на вищі напори (до 300 метрів) і при цьому отримати ширшу зону експлуатації не лише за витратами, а й за напорами. Використання здвоєних прямоточних гідроагрегатів дозволить істотно розширити експлуатаційні діапазони високоефективної та надійної роботи горизонтальних капсульних гідротурбін на витратах (потужностях), які дозволяють їм успішно функціонувати на змінних, пікових навантаженнях добового регулювання. На основі аналізу робочого процесу різних горизонтальних та діагональних турбін, аналізу їх універсальних характеристик було розроблено науково обґрунтовані пропозиції щодо номенклатури здвоєних прямоточних гідроагрегатів. Представлено конструкцію горизонтальної гідротурбіни з використанням підвідних соплових каналів. Застосування соплових апаратів як елементів, що створюють необхідний для оптимальної роботи гідротурбіни момент кількості руху, дозволяє використовувати капсульні прямоточні агрегати на високі напори (80–100 метрів).
Розробка горизонтальних капсульних гідротурбін на високі напори з широким діапазоном надійних режимів експлуатації
Keywords: bulb hydro turbine; runner; wicket gate; nozzle diaphragm; cate-blade relationship; efficiency; капсульні гідротурбіни; робоче колесо; направляючий апарат; сопловий апарат; комбінаторна залежність; коефіцієнт корисної дії